Research on the Knowledge ES Tool Based on Binary Tree - Qiu Yun; Fan Jingchao; Zhou Guomin (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
In the numerous agricultural information technologies, agricultural knowledge system has become an important part of the agricultural intelligent information technology (AIIT). This paper introduces the composition and working principle of the development tool for the binary tree-based knowledge system and uses one of the simplest examples to expound the operation method of the binary tree-based knowledge visualization editor and the development process of the accomplishment of the expert system for the apple disease diagnosis. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4492